Factors that influence students’ choice of private higher education institutions - Bezuidenhout, G.; de Jager, J.W.; Naidoo, V. (South African Journal of Higher Education, 2016)
Private higher education institutions (PHEIs) are important role players in the South African higher education landscape. Unlike their public counterparts, PHEIs receive no financial support from the government. These organisations are thus reliant on sound strategic management principles to ensure their long-term survival in a competitive industry. Modern marketing philosophy suggests that the consumer and the satisfaction of his or her needs should be the reason for the existence of any organisation and it should thus be the main driver for strategic decisions. This warrants the need for PHEIs to gain a thorough understanding of their clients (students) needs and behaviour. Very little research exists on the needs and behaviour of students registered at PHEIs in South Africa. The aim of this study was to determine the relative importance of various factors that influence students in their choice of a PHEI. In addition to an extensive literature study of the higher education landscape and its peculiarities, as well as student choice behaviour, a quantitative survey was conducted on 600 full-time students at three different PHEIs. It was found that, in contrast to numerous other studies, safety and security conditions constituted the most important choice factor amongst the respondents at the three PHEIs. Comparable to numerous international and local student choice studies, academic reputation and reasonable class fees were consistently identified as being very important choice factors. These findings should alert PHEIs to the important factors that should be considered in planning student offerings. This study contributes to existing student choice theory, and may serve as a launching pad for future student choice studies at PHEIs